Schopenhauer educatore? Storia e crisi di un'idea tra filosofia morale, estetica e antropologia - BORSARI, ANDREA (Studi e saggi, 2012)
The book investigates the reflection of Arthur Schopenhauer on education, calling to mind some of the great figures who have underlined his value as educator: Nietzsche of the Third Untimely Meditation, Hadot and Foucault of the Art of Living and Care of the Self; or, from the opposite perspective, the roles that were projected onto the philosopher as a teacher: aesthetic educator who was master of artistic contemplation for numerous generations of artists and writers between the nineteenth and twentieth centuries, master of wisdom, revealer of Eastern cultures, eudaemonological model of practical philosophy. The research also examines the recent renewed interest in «formation» (Bildung) in order to repropose the problem of how to return from the viewpoint of Schopenhauer's «anthropological results» to the very conceptual core - the relationship between the educational field and philosophical universe of Schopenhauer in connection with his notion of the human subject.